1994
DOI: 10.1016/0304-3959(94)90060-4
|View full text |Cite
|
Sign up to set email alerts
|

Sciatic entrapment neuropathy associated with an anomalous piriformis muscle

Abstract: Piriformis syndrome is an often overlooked cause of sciatica that typically responds to intramuscular local anesthetic and steroid injection. In this report, our patient presented with sciatica that responded poorly to epidural steroid injection and only transiently to piriformis injection. Surgical exploration of the sciatic nerve revealed a fascial constricting band around the nerve as well as a piriformis muscle lying anterior to the nerve. This unusual anatomical relationship between the piriformis and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(39 citation statements)
references
References 6 publications
1
37
0
1
Order By: Relevance
“…The type 6 variation defined hypothetically by Beaton and Anson [4] was later reported by Ozaki et al [14] and Sayson et al [20]. Similarly Babinski et al [2] and Mas et al [11] reported a rare variation, in which CFN and TN emerged as separate branches through the IP but TN was passing anterior to the superior gemellus muscle.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The type 6 variation defined hypothetically by Beaton and Anson [4] was later reported by Ozaki et al [14] and Sayson et al [20]. Similarly Babinski et al [2] and Mas et al [11] reported a rare variation, in which CFN and TN emerged as separate branches through the IP but TN was passing anterior to the superior gemellus muscle.…”
Section: Discussionmentioning
confidence: 85%
“…Many previous studies on the varied relationship between the piriformis and SN, have found variations in 15-30% of cases [17,20].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…22,33 This is probably the most common cause of PS. 13,22,33 Certain anatomic variants, such as double piriformis and course variants of the sciatic nerve, posterior cutaneous femoral nerve, inferior gluteal nerve, and superior gluteal nerve 4,5,7,14,15,26,27,40,41,60,61 can predispose to PS. 7,26,34,44 The presence of PS is frequently overlooked; the differential diagnosis is presented in Table 2.…”
Section: Pathophysiology and Etiologymentioning
confidence: 99%
“…Otras variaciones menos comunes reportadas en casos puntuales han sido caracterizadas como tipo VI de Beaton & Anson, donde el nervio isquiático pasa superiormente al músculo piriforme y desciende como un tronco común (Fig. 1E) presentado como un caso especial por Sayson et al, (1994) y por Ozaki et al (1999). Una disposición especial donde el nervio fibular común pasa debajo del músculo piriforme y el nervio tibial tiene un trayecto bajo el músculo gémino superior, fue reportada en un caso por Babinski et al (2003).…”
Section: Discussionunclassified